M-truncated optical soliton and their characteristics to a nonlinear equation governing the certain instabilities of modulated wave trains - Yusuf, Abdullahi; Sulaiman, Tukur A.; İnç, Mustafa; Abdel-Khalek, Sayed; Mahmoud, K. H. (Amer Inst Mathematical Sciences-Aims, 2021)
This study investigates the nonlinear Hamiltonian amplitude equation by using two analytical techniques, namely; the extended sinh-Gordon equation expansion method, and the extended rational sine-cosine/sinh-cosh methods. Some important wave solutions are successfully constructed, such as dark, bright, combined dark-bright, singular solitons, periodic and singular periodic wave solutions. The physical features of the acquired solutions are plotted to depict the clear dynamical behaviour of the reported results. All the acquired solutions have satisfied the original equation.
Keywords: Hamiltonian amplitude equation; extended sinh-Gordon method; extended rational sine-cosine/sinh-cosh; optical solitons; M-truncated derivative